1996
DOI: 10.1007/s004040050106
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma and amniotic fluid 17?-estradiol, progesterone and cortisol concentrations in women with successfully and unsuccessfully treated preterm labor

Abstract: Maternal plasma and amniotic fluid (AF) were obtained for measurement of 17 beta-estradiol, progesterone and cortisol concentrations from 40 patients with preterm labor and intact membranes at 28-32 weeks of gestation: 20 delivered preterm and the remaining 20 patients responded to tocolytic treatment and delivered at term. Maternal plasma and AF concentrations of these hormones were measured with specific commercially available radioimmunoassay kits. Maternal plasma and AF 17 beta-estradiol concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The sample collection took place between 6 weeks gestation and the end of the pregnancy. Some researchers used repeated samples for data collection throughout the women's pregnancies (Erickson et al, 2001; Hobel et al, 1999; Korebrits et al, 1998; McCool et al, 1994; Phocas et al, 1990; Ruiz et al, 2001; Sandman et al, 2006), whereas others collected data one time during the women's pregnancies (Field et al, 2004, 2006; Mazor et al, 1994, 1996; Mercer et al, 2006). Eight studies (53%) reported the time of day that the sample collection was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample collection took place between 6 weeks gestation and the end of the pregnancy. Some researchers used repeated samples for data collection throughout the women's pregnancies (Erickson et al, 2001; Hobel et al, 1999; Korebrits et al, 1998; McCool et al, 1994; Phocas et al, 1990; Ruiz et al, 2001; Sandman et al, 2006), whereas others collected data one time during the women's pregnancies (Field et al, 2004, 2006; Mazor et al, 1994, 1996; Mercer et al, 2006). Eight studies (53%) reported the time of day that the sample collection was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies suggested that maternal cortisol levels were positively related to preterm birth (Tables 1 and 2). Compared with women who gave birth full term, women who gave birth preterm had higher levels of cortisol (Erickson et al, 2001; Field et al, 2004, 2006; Hobel et al, 1999; Korebrits et al, 1998; Mazor et al, 1994, 1996; Mercer et al, 2006; Phocas et al, 1990; Sandman et al, 2006). However, the gestational age at the time of data collection seemed to influence the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In 1974 Csapo et al 3 found lower serum progesterone concentrations in 11 women with preterm labor than in 12 women with term labor. [4][5][6][7][8][9][10][11][12] Recent studies have found low saliva progesterone concentrations in women with preterm labor 13 and preterm delivery. [4][5][6][7][8][9][10][11][12] Recent studies have found low saliva progesterone concentrations in women with preterm labor 13 and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Recent studies have found low saliva progesterone concentrations in women with preterm labor 13 and preterm delivery. 3,6,9,11 Progesterone, estradiol, and estriol in relation to preterm delivery have mainly been investigated in singleton pregnancies 3,4,6,7,[9][10][11][12][13][14] and few results have been published from multiple pregnancies. 3,6,9,11 Progesterone, estradiol, and estriol in relation to preterm delivery have mainly been investigated in singleton pregnancies 3,4,6,7,[9][10][11][12][13][14] and few results have been published from multiple pregnancies.…”
Section: Introductionmentioning
confidence: 99%